Selecting a Name for a 4-H Club - Marilyn N. Norman; Joy C. Jordan (EDIS)
Each 4-H club is a unique group of young people working together toward common goals. A club name should reflect the purpose(s) of the club, and often relates to the project(s) the club participates in, the geographic area where members live, or where the club meets. One of the first ways to develop a sense of belongingness and youth engagement is allowing all of the members to participate in selecting a name for the club. Information in this sheet may help guide members in making a wise choice. This document is 4HS FS101.7, one of a series of the 4-H Youth Development Department, UF/IFAS Extension. Published May 2006.